Effects of Mental Disorders on Fibromyalgia Mediated by Insomnia: A Mendelian Randomization Study - Chang L; Sun Z; Zeng S; Huang C; Cai Z (Journal of Pain Research)
Le Chang,1 Zhen Sun,1 Shiyong Zeng,2 Canyang Huang,3 Zhenyu Cai3 1Department of Clinical Medicine, Quanzhou Medical College, Quanzhou, Fujian, People’s Republic of China; 2Medical Research Center of Quanzhou Medical College, Quanzhou, Fujian, People’s Republic of China; 3Department of Orthopedics, Quanzhou First Hospital Affiliated to Fujian Medical University, Quanzhou, Fujian, People’s Republic of ChinaCorrespondence: Zhenyu Cai, Email czyzone@126.comBackground: This study employed Mendelian randomization (MR) analysis to confirm the causal effects of mental disorders on fibromyalgia.Methods: The summary data for exposures, mediator, and outcome were extracted from the GWAS catalog project, IEU openGWAS project, and Finn biobank database. Significantly associated and independent single-nucleotide polymorphisms (SNPs) meeting the criteria of p < 5× 10− 8, r2 < 0.001, and kb = 10,000 were selected for MR analysis. We used univariate and multivariate Mendelian randomization (i) to investigate the causal relationship between mental disorders/insomnia and fibromyalgia and (ii) to examine the mediating role of insomnia. The inverse variance weighted (IVW) method along with other MR methods was employed for analysis, while sensitivity analyses were conducted to assess reliability and stability.Results: The results provided strong evidence to confirm the causal and positive associations between depression (OR = 6.749; 95% CI: 2.293– 19.868, P = 0.001), irritability (OR: 1.873, 95% CI: 1.023− 3.428, P = 0.042), insomnia (OR: 8.395, 95% CI: 1.384− 50.931, P = 0.021), and fibromyalgia. Moreover, a positive causal relationship was detected between depression (OR = 1.230; 95% CI: 1.178– 1.285; P < 0.001), irritability (OR = 1.084; 95% CI: 1.046– 1.122; P < 0.001) and insomnia. Multivariate Mendelian randomization analysis showed that insomnia mediated the effects of depression and irritability on fibromyalgia, and the proportion of insomnia-mediated cases ranged from 25.2% to 26%.Conclusion: This study showed a positive causal relationship between depression, irritability, insomnia, and fibromyalgia. Insomnia partly mediates this overall effect. Understanding the causal relationship between mental disorders and fibromyalgia and the mediating role of insomnia may provide more information for fibromyalgia intervention and prevention strategies.Keywords: mental disorders, fibromyalgia, insomnia, Mendelian randomization, mediation